2009
DOI: 10.1074/jbc.m901026200
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoprotein G Regulates Splice Site Selection by Binding to CC(A/C)-rich Regions in Pre-mRNA

Abstract: Almost every protein-coding gene undergoes pre-mRNA splicing, and the majority of these pre-mRNAs are alternatively spliced. Alternative exon usage is regulated by the transient formation of protein complexes on the pre-mRNA that typically contain heterogeneous nuclear ribonucleoproteins (hnRNPs). Here we characterize hnRNP G, a member of the hnRNP class of proteins. We show that hnRNP G is a nuclear protein that is expressed in different concentrations in various tissues and that interacts with other splicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
139
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(148 citation statements)
references
References 51 publications
9
139
0
Order By: Relevance
“…In previous experiments, fractions corresponding to the analogous positions in the gradient were enriched for the five spliceosomal U snRNAs (37,(39)(40)(41) (Fig. S1D), various pre-mRNAs (36,42,43), and regulatory splicing factors (41,44,45) (Fig. 1E) and contained active spliceosomes (37).…”
Section: Resultsmentioning
confidence: 99%
“…In previous experiments, fractions corresponding to the analogous positions in the gradient were enriched for the five spliceosomal U snRNAs (37,(39)(40)(41) (Fig. S1D), various pre-mRNAs (36,42,43), and regulatory splicing factors (41,44,45) (Fig. 1E) and contained active spliceosomes (37).…”
Section: Resultsmentioning
confidence: 99%
“…As it is well known that many alternative splicing factors, including hnRNP G and hTra2-beta1, are shuttling intracellularly between nucleus and cytoplasm, it is of large interest to further investigate the mechanism which influences or actively regulates cellular splicing factors shuttling. Both hnRNP G and hTra2-beta1 are sequence-specific splicing factors 21,25,37 and are potentially capable to exert opposite effects on expression of alternative spliced genes in a concentration-dependent manner. 25 HnRNP G preferentially regulates alternative exons where a AAGU or CC(A/C) containing motif is clustered.…”
Section: Discussionmentioning
confidence: 99%
“…25 HnRNP G preferentially regulates alternative exons where a AAGU or CC(A/C) containing motif is clustered. 25,37 A panel of tumor biological important genes are regulated through hTra2-beta1 mediated GAA-rich enhancer-dependent splicing. 21 CD44, ESRa, BRCA1, scr, Her2/neu are such genes regulated by hTra2-beta1, which play important roles especially in hormone-dependent malignancies such as breast and ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on the host factors that associate with host chromosomes, because our previous study demonstrated that the formation of vSPOTs, as well as the dynamics of viral RNPs, appeared to be associated with the structural dynamics of chromosomes, such as mitosis (Heinrich et al, 2009;Matsumoto et al, 2012). Among the candidate host factors (Table S1, available in the online Supplementary Material), we focused on a nuclear protein, RBMX, because only this protein has been shown to be associated with chromosomal structure and to form nuclear foci (Heinrich et al, 2009).…”
mentioning
confidence: 99%
“…Among the candidate host factors (Table S1, available in the online Supplementary Material), we focused on a nuclear protein, RBMX, because only this protein has been shown to be associated with chromosomal structure and to form nuclear foci (Heinrich et al, 2009). RBMX is an RNA-binding protein that participates in the spliceosome and plays a role in alternative splicing (Heinrich et al, 2009).…”
mentioning
confidence: 99%